2022
DOI: 10.1108/aaaj-07-2021-5382
|View full text |Cite
|
Sign up to set email alerts
|

It's a gift – Samuel Pepys and Sir William Warren, an account of gifts, bribes and kickbacks

Abstract: Purpose This study aims to investigate an individual’s boundary crossing with regard to bribery, gifts and favouritism in rewarding contracts. Samuel Pepys’s diary was written in the 17th century and through detailed accounts gives insight into his inherent professionalism and his negative opinions around bribery but also his acceptance of “gifts” and awarding of contracts to “friends”.Design/methodology/approach The research uses a narrative approach to study a detailed and reflective personal diary identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…We use emancipatory accounting theory (Gallhofer and Haslam, 2002, 2006, 2019) as the lens through which we analyse the company accounts, with analysis following a framework suggested by Atkins and Maroun (2018). In this way, this microhistory (Carnegie and McBride, 2022) uses theory to provide a conceptual framework (Carnegie and Napier, 2017) for historical narrative (McBride, 2023), exploring how sets of accounts and company reporting can illustrate an approach to integrated business, reporting and management of ecology.…”
Section: Introductionmentioning
confidence: 99%
“…We use emancipatory accounting theory (Gallhofer and Haslam, 2002, 2006, 2019) as the lens through which we analyse the company accounts, with analysis following a framework suggested by Atkins and Maroun (2018). In this way, this microhistory (Carnegie and McBride, 2022) uses theory to provide a conceptual framework (Carnegie and Napier, 2017) for historical narrative (McBride, 2023), exploring how sets of accounts and company reporting can illustrate an approach to integrated business, reporting and management of ecology.…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis we take an interpretive view and analyse the text in a similar way to earlier work which explores historic discourse, for example Atkins et al (2014) in their analysis of William Morris' varied works, Atkins and McBride (2021) in studying Fumifugium as an historical environmental report and McBride (2023) interpreting a case study found within a diary. Milne et al (2009) explored the analysis of dialogue in a critical and interpretive manner.…”
Section: Introductionmentioning
confidence: 99%